Development of Learning Media using iSpring Presenter Based HOTS-Literacy on Acid-Based Materials - Anisa Nursalsabillah Nasution; Iis Siti Jahro (Universitas Negeri Medan, 2023)
In the 21st century, education is becoming increasingly important to ensure students have learning and innovation skills, skills in using information technology and media, and can work and survive using life skills. One of the life skills that students must have now is HOTs-literacy. This research aims to (1) to find out learning media used in learning process; (2) to design a prototype that will be developed to produce a learning media based on HOTs-literacy; (3) to find out whether the learning media that has been developed meets the criteria; (4) to find out student responses to the media. The method used in this research is 4D model. The result: Based 5 validators it was found 86.6% with a very high Percent Interpretation and a “Eligible” level of eligibility of the media and for the student responses get 95.71% with “very interesting” level. This shows that the HOTS-Literacy-based learning media using iSpring on acid-base material that has been developed is very attractive to students, so it can be used as a supporting medium in learning chemistry.